Computational science -- ICCS 2007 [electronic resource]: Part III: 7th international conference, Beijing, China, May 27-30, 2007 : proceedings - ICCS 2007 (2007 : Beijing, China); Shi, Yong, 1956-; SpringerLink (Online service) (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
57